Caring Behavior of novice nurses: basis for staff development program/ Michel Gem M. Canate, and Rosie N. Guimban. - Canate, Michel Gem M.; Guimban, Rosie N. (Paranaque City; Olivarez College, 2011)
The present study explored into the caring behavior of novice nurses in a selected government hospital. The tool given out was rated by the patients handled by the novice nurses. Data acquired were used as basis to formulate a staff development program. Specific questions that this study aimed to answer are (1) what is the profile of the novice nurses in terms of gender and area of assignment, (2) to what extent do the novice nurses manifest caring behaviors in terms of compassion, competence, confidence, conscience, commitment, and comportment, (3) is there a significant difference between the profile of the novice nurses and their caring behaviors, and (4) what program can be developed for novice nurses. The study used a descriptive research design. Using a purposive sampling technique, target respondents were obtained. The respondents are novice nurses who have 0 to 2 years of experience in the selected government hospital. The validated survey was used to gather the variables needed for the study. Descriptive statistics (means and frequency and percentage) was utilized, so were inferential statistics that include analysis of variance (ANOVA) and t-test. General findings revealed that the novice nurses caring behaviors in terms of compassion, competence, confidence, conscience, commitment, and comportment ranges from 3.95 to 4.32 means. These values signify that the caring behaviors exhibited by the novice nurses are perceived from a high to a very high extent. Comportment was particularly high with its sub-items gaining means that range from 4.26 to 4.38, all signifying that the perceived caring behaviors are to a very high extent. Furthermore, the result gathered from the study regarding the difference of novice nurses' caring behaviors from gender profile, t-value of 0.97 was acquired concluding the decision that there is no significant difference between the perceptions of respondents when grouped according to gender. Oppositely, the data gathered from the study that inquires the difference between the perceptions of respondents when grouped according to area of assignment showed an F value of 6.63, concluding the decision that there is a significant difference when caring behaviors of novice nurses were grouped according to area of assignment. A staff development program was formulated based on the findings gathered from the study that determined the strengths and weaknesses of novice nurses in terms of caring behaviors Basing on the results of the study, the following are hereby recommended: (1) that caring behaviors of novice nurses be continuously assessed as part of their regular performance appraisal utilizing patient feedback, self-evaluation and supervisor's evaluation facilitated by the developed program. Feedback with the results should be immediately regarded for personal and professional growth of the novice nurses (2) that seminars and training programs be instituted to further the abilities of the novice nurses focusing on active listening, communication skills, basic independent nursing skills, personality development, patient advocacy, and transcultural practice, (3) that activities to sustain strengths of novice nurses on proper grooming, patient rounds, respecting one's decisions. health teaching, unconditional positive regard to patients and medication administration be developed, (4) that the proposed staff development program be tested for its effectiveness and consequently be utilized for novice nurses and (5) that a similar study be conducted utilizing the variables indicated in this research covering a larger sample, employing various methodologies and on a different locale for further evaluation.
Undergraduate Thesis